EFEKTIVITAS KEBIJAKAN PEMERINTAH MENGENAI PEMBELAJARAN DARING DI KALANGAN MAHASISWA - Purnamaningsih Purnamaningsih; Wismayanti Wismayanti (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2021)
The Covid-19 pandemic in Indonesia has had a huge impact on various sectors of people's lives, especially in the world of education. One of the policies made by the government in overcoming educational problems in the midst of a pandemic, the government took a policy to implement distance learning or online as an effort to overcome education in the midst of a pandemic. Distance learning is a process of learning activities that are not carried out in one place at the same time but carried out in different places through online. This study aims to see the effectiveness of online learning among students. This study uses descriptive research with qualitative methods where this method describes the problem under study clearly by reviewing and describing the existing data in detail and systematically. Data collection techniques were carried out by indirect and direct interviews. Sources of data used are secondary and primary data. This study uses indirect interviews in the form of a questionnaire with 100 respondents by giving 5 questions. The results of this study indicate that 56% of students responded that they were quite satisfied with online learning. The media used in online learning 90% said using webex. The material presented in the learning process was quite well received by students. The obstacles faced by students in online learning showed that 48% did not understand the material presented.And the results of the latest research show 64% of respondents said the online learning process is quite effective.